This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
how come substituting 0 to original equation does not preserve the equality? A complex number raised to 0 is 1 right? So wouldn't substituting x with 0 equal to:
0 = 1 + 1 + 1
0 = 3
Is there something wrong with my logic?
Log in to reply
Thanks. I have updated the answer to 3 only.
The mistake made in @Ahmad Hesham 's solution is that he initially multiplied by x , which introduced the extraneous solution x = 0 .
Log in to reply
Well , what I really did was multiplying by ω x However, the solution x = 0 actually doesn't satisfy the equation and it's my fault , sorry about it
Hello from my knowledge at the point where we get the solutions as 0 or 3, we have to choose which is applicable. Usually while solving a quadratic we used to get multiple answers but then we prioritize those and select the actual answer. So I think the answer is only 3 because substituting 0 is not making any sense.
Log in to reply
FYI - To type equations in Latex, you just need to add \ ( \ ) around your math code, as opposed to all of the text. In this way, you don't have to use \quad all the time.
EXTREMELY bad choice of options.
See that x = 0 does NOT satisfy the condition, because it will lead to 0 = 3 , impossible.
Only 1 option does NOT contain 0 -_-
Problem Loading...
Note Loading...
Set Loading...
x = 1 + ω x + ω 2 x → ( 1 ) B y m u t i p l y i n g b y ω x : x ω x = ω x + ω 2 x + ω 3 x ∵ ω 3 x = 1 ∴ x ω x = ω x + ω 2 x + 1 → ( 2 ) F r o m ( 1 ) , ( 2 ) : x = x ω x x − x ω x = 0 x ( 1 − ω x ) = 0 ∴ x = 0 O r ω x = 1 ∴ x = 3 N o w t h e r e ′ s s o m e t h i n g I m i s s e d w h i c h o n e o f t h e s o l v e r s n o t i f y m e a b o u t : ) ∗ I f y o u t r i e d i t , y o u ′ d f i n d o u t t h a t { x = 0 } d o e s n ′ t s a t i s f y t h e e q u a t i o n b e c a u s e i f y o u s u b s t i t u t e x w i t h 0 y o u ′ l l h a v e : 0 = 1 + 1 + 1 0 = 3 w h i c h i s r e j e c t e d o f c o u r s e S o w e ′ d c o m e u p w i t h x = 3 a s a f i n a l s o l u t i o n